Comparison of unmodified and modified BCR sequential extraction schemes for the fractionation of heavy metals in shrimp aquaculture sludge from Selangor, Malaysia - Nemati, K.; Bakar, Nor Kartini Abu; Abas, M.R.; Sobhanzadeh, E.; Low, K.H. (2011)
A study was carried out to investigate the fractionation of Cd, Cr, Cu, Fe, Mn, Pb, and Zn in shrimp aquaculture sludge from Selangor, Malaysia, using original (unmodified) and modified four-steps BCR (European Community Bureau of Reference, now known as the Standards Measurements and Testing Program) sequential extraction scheme. Step 2 of the unmodified BCR procedure (subsequently called Method A) involves treatment with 0.1 M hydroxylammonium chloride at pH 2, whereas 0.5 M hydroxylammonium chloride at pH 1.5 was used in the modified BCR procedure (subsequently called Method B). Metal analyses were carried out by flame atomic absorption spectrometry. A pseudo-total aqua-regia digest of BCR CRM 701 has also been undertaken for quality assurance purposes. The recovery of Method A for all metals studied ranges from 96.14 to 105.26, while the recovery for Method B ranges from 95.94 to 122.40. Our results reveal that Method A underestimated the proportion of metals bound to the easily reducible fraction except for copper. Therefore, the potential mobility of these elements is higher than others. Thus, to use this sludge as a fertilizer we have to first find a remediation for reduction of heavy metal contamination.